Impact of material properties for improved Pseudomonas aeruginosa biofilm inactivation with 280 nm UV LEDs - Toni J. Mullin; Sean A. MacIsaac; Amina K. Stoddart; Graham A. Gagnon (Scientific Reports)
Abstract Biofilm microbial communities encased in extracellular polymeric substances are a concern in drinking water premise plumbing and fixtures, and are challenging to remove and disinfect. Pseudomonas aeruginosa (P. aeruginosa), a commonly used surrogate organism, is employed in this study due to its widely documented occurrence in biofilms within drinking water systems. This study investigates 280 nm UV light emitting diodes (UV LEDs) for inactivating P. aeruginosa biofilms grown on common plumbing materials extruded Polytetrafluoroethylene, Acrylonitrile Butadiene Styrene, Viton®, Silicone, High Density Poly Ethylene, Stainless Steel, Porex (expanded PTFE), and Polycarbonate. Biofilms were cultivated in CDC biofilm reactors on 12.8 mm diameter coupons and then exposed to UV LED light at fluences ranging from 5 to 40 mJ/cm2 with log reduction values between 0.851 and 2.05 CFU/cm2 for Viton® (k = 0.133 ± 0.0625 cm2/mJ) and Silicone (k = 0.344 ± 0.145 cm2/mJ), respectively. This research demonstrates that material properties influence biofilm formation and the subsequent effectiveness of UV LED inactivation while illustrating that characteristics such as surface roughness and reflectivity significantly impact inactivation. This work advances the understanding of biofilm inactivation under UV LED exposure, thereby aiding in the development of more effective biofilm inactivation strategies.